2000
DOI: 10.1212/wnl.55.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in sporadic inclusion body myositis: Observations in 78 patients

Abstract: Functional decline for each decade at symptom onset and need for cane, walker, or wheelchair were assessed in 78 biopsy-proved patients with sporadic inclusion body myositis. Patients with disease onset between 40 and 59 years used a walker after 10.2 +/- 5.8 years, whereas those with disease onset between 60 and 79 years used a walker after 5.7 +/- 5.0 years (p = 0.05). Because patients progress faster to disability when symptoms begin after the age of 60, age at disease onset may define patient subsets for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 9 publications
7
65
0
3
Order By: Relevance
“…This is in contrast to the common conception in neuromuscular disorders that tend to be more disabling with earlier onset such as in dystrophinopathies and spinal muscular atrophy. A previous study also suggested faster progression to disability in patients with onset beyond 60 years of age [17]. As age of onset is an independent predictor of progression this finding needs to be taken into account in the design of future treatment trials.…”
Section: Discussionmentioning
confidence: 90%
“…This is in contrast to the common conception in neuromuscular disorders that tend to be more disabling with earlier onset such as in dystrophinopathies and spinal muscular atrophy. A previous study also suggested faster progression to disability in patients with onset beyond 60 years of age [17]. As age of onset is an independent predictor of progression this finding needs to be taken into account in the design of future treatment trials.…”
Section: Discussionmentioning
confidence: 90%
“…Once diagnosed, treatment is usually of the supportive nature rather than curative because IBM does not respond to typical immunosuppressive treatments [3,8,9]. Current treatments aim to slow the rate of progression of the disease rather than cure it [5,10]. True treatment efficacy is difficult to gauge, however, because of the relatively slow progression, rate of progression differing between patients, and the fact that older patients tend to decline more rapidly, although the reason for this is not entirely clear [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Strength usually decreases 5-10% per year, although rates of progression can vary [3,10,12]. Yet most patients remain ambulatory for many years after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The amyotrophy can be asymmetric, and in typical cases muscle weakness and wasting are most profound in knee extensors, hip flexors and long finger flexors 8 . Most patients require an assistive device within several years of onset 9 . Neck flexors and extensors and facial muscle are frequently affected 8 .…”
Section: Discussionmentioning
confidence: 99%